Insight into NiCo-based nanosheets modified MnS/Mn0·2Cd0·8S hybrids for enhanced visible-light photocatalytic H2 evolution. (5th April 2022) - He, Xianglong; Zeng, Qingru; Zheng, Hongfei; Ong, Wee-Jun; He, Yuxin; Huang, Bangwei; Li, Linji; Zeng, Deqian
Abstract: Bimetallic compounds nanocrystals exhibited great potential in catalysis due to the synergistic effects and encouraging performance. Herein, a series of NiCo-based nanosheets, including NiCo LDH/NiCo(OH)2, NiCo, and NiCo2 O4, have been developed to modify MnS/Mn0·2 Cd0·8 S (MMCS) nanoparticles for photocatalytic H2 production under visible light (λ > 420 nm). The two-dimensional (2D) NiCo2 O4 and NiCo were derived from the oxidation and reduction process of the as-prepared NiCo LDH/NiCo(OH)2 nanosheets, respectively. MMCS nanoparticles were prepared using a one-pot solvothermal method and then integrated into three different NiCo-based nanosheets through a simple hybridization approach. Compared to pure MMCS, the resultant NiCo-based nanosheets/MMCS hybrids show dramatically improved visible-light photocatalytic activities. Moreover, among the three types of composites, NiCo2 O4 -MMCS (7%NiCo2 O4 -MMCS) displays the highest H2 production rate of 3.31 mmol g −1 h −1 with the apparent quantum efficiency of 6.42% at 420 nm, approximately 22 and 5 times that of pure MMCS (0.15 mmol g −1 h −1 ) and Pt/MMCS (0.67 mmol g −1 h −1 ), respectively. The remarkably enhanced photocatalytic activities of the NiCo LDH/NiCo(OH)2 -MMCS, NiCo-MMCS, and NiCo2 O4 -MMCS are mainly ascribed to the formed type-II, Schottky, and p-n heterojunctions, respectively, which efficiently boost photogenerated charge carrier separation and migration. In this paper, we intensively investigate the roles of three different NiCo-based nanosheets in the Mnx Cd1-x S-based system. This work provides an effective strategy to design and construct the innovative 2D bimetallic compounds-based catalysts for high-efficiency photocatalytic H2 production. Graphical abstract: The existence of type-II, Schottky, and p-n heterojunctions for NiCo LDH/NiCo(OH)2 -MMCS, NiCo-MMCS, and NiCo2 O4 -MMCS boosted the transfer of photogenerated carriers. This work provides important insights into the various heterojunctions based on the NiCo-based nanosheets and suitable visible-light-responsive semiconductors toward high-efficiency photocatalytic water splitting. Image 1 Highlights: MnS/Mn0·2 Cd0·8 S (MMCS) were prepared via a one-pot solvothermal approach. NiCo-based nanosheets modified MMCS exhibited enhanced photocatalytic activity. NiCo2 O4 -MMCS composite exhibited the highest photocatalytic H2 production rate. The heterojunctions of three different MMCS-based composites were investigated.